A Pilot Study on the Whole Exome Sequencing of Prostate Cancer in the Indian Phenotype Reveals Distinct Polymorphisms - Gupta, Ayam; Shukla, Nidhi; Nehra, Mamta; Gupta, Sonal; Malik, Babita; Mishra, Ashwani Kumar; Vijay, Maneesh; Batra, Jyotsna; Lohiya, Nirmal Kumar; Sharma, Devendra; Suravajhala, Prashanth (Frontiers in Genetics, 2020)
Prostate cancer (PCa) is a common cancer among men, and yet no next generation sequencing (NGS) studies in India have been attempted earlier. Recent advances in NGS have heralded the discovery of biomarkers from Caucasian/European and Chinese ancestry but not much is known about Indian phenotype/variant of PCa. In a pilot study using the whole exome sequencing of benign/PCa patients, we identified characteristic mutations specific to Indian sub-population. We observed a large number of mutations in DNA repair genes, viz. helicases, TP53 and BRCA besides the variants of unknown significance (VUS) with a possibly damaging rare variant (rs730881069/chr19:55154172C/TR136Q) in the TNNI3 gene that has been previously reported as a semi-conservative amino acid substitution. While we delved into these polymorphisms, we believe these observations are prelude to warrant further research in bringing better understanding of PCa prognosis and recurrence for Indian phenotype.